Does Profit-Seeking Rule Out Love? Evidence (or Not) from Economics and Law - Julie A. Nelson (Washington University Journal of Law & Policy, 2011)
In this Essay, the author presents the belief that business enterprises are driven to maximize their profits and will not take action benefiting their workers, communities or environment at the cost of reduced profitability. It describes the economic theory of profit maximization, examines the use of profit maximization and presents the history and philosophy of economics. It also suggests that the phenomenon of love and money must be considered to create a more humane economy.
Keywords: Law & amp; behavioral economics; Corporate governance; Stockholders; Executive compensation; Commoditization; Law and economics (Jurisprudence); Organizational behavior; Sustainable growth (Business); United States; Organizational behaviour